2012
DOI: 10.1002/clc.22088
|View full text |Cite
|
Sign up to set email alerts
|

Infarct‐like Acute Myocarditis: Relation Between Electrocardiographic Findings and Myocardial Damage as Assessed by Cardiac Magnetic Resonance Imaging

Abstract: Background: Acute myocarditis (AM) may occasionally have an infarct-like presentation. The aim of the present study was to investigate the relation between electrocardiographic (ECG) findings in this group of patients and myocardial damage assessed by cardiac magnetic resonance imaging (MRI) with the late gadolinium enhancement (LGE) technique. Hypothesis: Myocardial damage may be associated with ECG changes in infarct-like AM. Methods: Forty-one consecutive patients (36 males; mean age, 36 ± 12 years) with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
20
0
1
Order By: Relevance
“…A clear territorial distribution on ECG is not always visible. No strict correlation was found between location of ST elevation on surface ECG and areas of distribution of necrosis/scar as assessed by MRI in LGE sequences (Deluigi et al, 2013;Di Bella et al, 2012;Nucifora et al, 2013). A study by Karjalainen et al showed that, in young men with ACS-like myocarditis, patients with larger extension of myocardial damage (as assessed by peak creatine kinase MB value) had higher maximum ST elevation in a single lead (Karjalainen & Heikkilä, 1986).…”
Section: F I G U R Ementioning
confidence: 99%
“…A clear territorial distribution on ECG is not always visible. No strict correlation was found between location of ST elevation on surface ECG and areas of distribution of necrosis/scar as assessed by MRI in LGE sequences (Deluigi et al, 2013;Di Bella et al, 2012;Nucifora et al, 2013). A study by Karjalainen et al showed that, in young men with ACS-like myocarditis, patients with larger extension of myocardial damage (as assessed by peak creatine kinase MB value) had higher maximum ST elevation in a single lead (Karjalainen & Heikkilä, 1986).…”
Section: F I G U R Ementioning
confidence: 99%
“…[ 91 93 ] Infectious myocarditis patients can present with additional infarct-like symptoms such as ST-segment elevation on ECG, wall motion abnormalities, and elevated circulating cardiac troponin levels. [ 94 , 95 ] However, despite the similarities in clinical presentation, infectious myocarditis and myocardial infarction are generally considered as distinct clinical entities.…”
Section: Effects On Coronary Artery Atherosclerosismentioning
confidence: 99%
“…Even though ventricular tachycardia is often associated with a poor prognosis in human cases of myocarditis caused by Chagas disease, and with increased risk of sudden death [37], the presence of major arrhythmias was not considered a risk factor for the animals who died in this study since the animal that presented severe arrhythmias survived for the entire 28-day follow up period.…”
Section: Discussionmentioning
confidence: 99%